Novel 3D-printed polycaprolactone/gelatin based biopatches loaded with natural antibacterial agents for hernia treatment - Uysal, Ebru; Enguven, Gozde; Ege, Hasan; Deveci, Mehmet Zeki; Yontem, Fulya Dal; Agturk, Gokhan; Evran, Savas; Alakus, Ibrahim; Kirgiz, Omer; Akcakavak, Gokhan; Akcakavak, Filiz Kazak; Alakus, Halil; et al. (IOP Publishing Ltd, 2026)
Incisional hernia is a common postoperative complication, particularly following abdominal surgeries, and is frequently associated with recurrence and impaired healing due to postoperative infections. In this study, a dual-layered hernia repair biopatch was developed by integrating a 3D-printed polycaprolactone/gelatin (PCL/Ge) scaffold, providing mechanical support, with an electrospun nanofibrous layer composed of PCL/Ge/kappa-carrageenan (kappa-C) to promote wound healing. To impart antimicrobial functionality, the scaffolds were functionalized with either Agrimonia eupatoria (AE) extract or the clinically used antibiotic rifampicin (RIF). Commercial polypropylene (PP) meshes were employed as control groups in both in vitro and in vivo evaluations. Mechanical testing demonstrated that the developed biopatches exhibited tensile strengths within a clinically relevant range, with values of 5.13 MPa and 2.49 MPa for the 3D-printed RIF-loaded and AE-loaded electrospun-coated scaffolds, respectively. Both AE- and RIF-loaded groups showed pronounced antibacterial activity against S. aureus, a predominant pathogen associated with surgical site infections. Sustained and controlled release profiles were observed over 160 h, with cumulative release values of approximately 30%-35%. In vivo evaluation using a rat incisional hernia model revealed that AE exhibits strong potential as an alternative to conventional antibiotics, attributable to its phenolic-rich composition and associated anti-inflammatory and tissue-remodeling properties. Overall, these findings demonstrate that the proposed dual-layer biopatch, which integrates mechanical reinforcement with sustained antimicrobial activity, represents a promising and effective strategy for infection-resistant incisional hernia repair.
Keywords: hernia repair; polycaprolactone; Agrimonia eupatoria; rifampicin; antibacterial; tissue regeneration; 3D printing; MECHANICAL-PROPERTIES; TISSUE; REPAIR; Engineering; Materials Science